2014
DOI: 10.2224/sbp.2014.42.8.1267
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Employee Emotions in the Relationship Between Authentic Leadership and Employee Innovation

Abstract: Although researchers emphasize that the construct of authentic leadership (AL) is relevant to resolving different kinds of failures and inadequacies of leadership, it remains unknown whether or not, and how, authentic leadership style intrinsically evokes employees' innovation. Using multilevel data from 76 teams sourced from 5 enterprises in China, we applied hierarchical linear modeling and found a positive relationship between AL and employees' innovation. Employees' positive emotions were found to have a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 24 publications
(54 reference statements)
6
49
0
Order By: Relevance
“…Thus, authenticity involves the action of persons according to their values. In other words it is for a person to tell what he believes or thinks and act accordingly [3,10,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, authenticity involves the action of persons according to their values. In other words it is for a person to tell what he believes or thinks and act accordingly [3,10,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Ilies et al [10] discuss influence of authentic leadership on eudaemonic well-being. Positive relationship were found between authentic leadership and ethical leadership, organizational behavior, commitment, satisfaction, trust in leader, positive emotions, internal whistleblowing, innovation, creativity, moral courage, structural empowerment, self-related performance [3,8,9,14,18,19,20,21].…”
Section: Authentic Leadershipmentioning
confidence: 96%
See 1 more Smart Citation
“…It is also interesting to note that although there is a good degree of theorizing regarding affect and creativity, there is little regarding innovation. The few studies that have explored the relationship between affect and innovation show promising links (e.g., Zhou, Ma, Cheng, & Xia, 2014), and so this looks like a fruitful avenue for future research.…”
Section: Insert Figure 2 About Herementioning
confidence: 99%
“…Thus, authentic leadership can enhance employees' sense of control. Secondly, research has shown that authentic leadership can increase employees' psychological capital (i.e., self-efficacy, optimism, hope and resilience) (Rego et al 2012(Rego et al , 2016 and can also increase their positive emotions (Hsiung 2012;Zhou et al 2014). According to the conservation of resources theory, adequate psychological resources are essential for people to control their emotions; thus, it is reasonable to argue that authentic leadership can increase people's emotional stability.…”
Section: The Mediating Role Of Core Self-evaluationsmentioning
confidence: 99%